Xanthippos. From Alexandria to Callinicum (260-244 BC) - Hauben, Hans (Chronique d’Égypte, 2024)
Abstract Xanthippos, the friend of the architect Kleon; Xanthippos, the trierarch of an expensive ‘nine’ in the harbor of Halicarnassus (Pros. Ptol. V 14110); Xanthippos, the ephemeral governor of the Upper Satrapies (Pros. Ptol. VI 15060) - all three, showing corresponding social and military profiles, were one and the same person. Xanthippos' career in the service of the early Ptolemies extended over a period of more than fifteen years (260-244), strikingly coinciding with that of Apollonios the dioike ête ês (261-245). Any link with the Spartan commander who, as the champion of the Carthaginian cause expelled a Roman army from African soil, should be discarded. It would be absurd to suppose that the Alexandria-based gentleman of January 260, Ptolemaic trierarch in 258-257, had settled in Sparta before meddling in the First Punic War by May 255.